Electromagnetic Characterization of a Composite (RE-CB-MT) by Time Domain Spectroscopy - Amina Bounar; Nacerdine Bouzit; Nacerdine Bourouba (Advances in Materials Science and Engineering)
The aim of this article is to study the dielectric behavior (ε, σ) in microwaves domain of composites made with Epoxy Resin (RE), Carbon Black (CB), and Magnesium Titanate (MT) on a large band of frequency. This kind of composites is very solicited for applications and miniaturization of the components circuits (cavities, antennas, substrates, etc.) in hyperfrequency electronics. In this study we have also highlighted the effect of the fillers nature and their concentrations on the behavior of these composites. The results obtained by time domain spectroscopy (TDS) have revealed the strong dependence of complex permittivity of the composite materials on both the nature and the concentration of conductive environment. Low frequency analysis (500 MHz) has been investigated to determine the conductivity of composites which is related to the percolation phenomenon. Moreover, the comparison between experimental results and theoretical models shows that the modeling Lichtenecker law is applicable to the ternary mixture in this frequency range and is in accordance with the approach postulated by Bottreau.